Intercultural Masquerade New Orientalism, New Occidentalism, Old Exoticism - Machart, Regis; Dervin, Fred; Gao, Minghui (Encounters between East and West, Intercultural Perspectives, 2016)
XVI, 147 p. 1 illus.